2021
DOI: 10.1186/s43044-021-00210-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ductus arteriosus stenting including vertical tubular and convoluted tortuous ducts with emphasis on technical considerations

Abstract: Background Ductal stenting is the preferred method of securing adequate pulmonary blood flow in patients with duct-dependent pulmonary circulation. The main limitation in most centers is the difficult vertical tubular or convoluted ducts that represent real challenges to interventional pediatric cardiologists. We present our experience in patent ductus arteriosus (PDA) stenting with some technical tips to overcome difficulties, especially in stenting tortuous or long tubular ducts. This study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, this assumption has been challenged by recent studies that demonstrated successful stenting for a variety of morphologies. 25,31,32 Technical considerations are important in these cases of convoluted ducts or those with difficult origin. Some investigators prefer deploying multiple overlapping stents to ensure full coverage in tackling a tortuous PDA, 31 whereas others prefer to use 1 long stent.…”
Section: Tortuosity and Feasibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…However, this assumption has been challenged by recent studies that demonstrated successful stenting for a variety of morphologies. 25,31,32 Technical considerations are important in these cases of convoluted ducts or those with difficult origin. Some investigators prefer deploying multiple overlapping stents to ensure full coverage in tackling a tortuous PDA, 31 whereas others prefer to use 1 long stent.…”
Section: Tortuosity and Feasibilitymentioning
confidence: 99%
“…25,31,32 Technical considerations are important in these cases of convoluted ducts or those with difficult origin. Some investigators prefer deploying multiple overlapping stents to ensure full coverage in tackling a tortuous PDA, 31 whereas others prefer to use 1 long stent. 13 However, both stress the importance of covering both ends of the PDA and not leaving a portion unstented.…”
Section: Tortuosity and Feasibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies described procedural considerations and explained their techniques. The precise attention to detail of these techniques and tips and tricks is critical for ensuring the greater success of ductus arteriosus stenting (1,7).…”
Section: Introductionmentioning
confidence: 99%